Prevalence of “Compressed” and Asymmetric Lateral Ventricles in Healthy Full-Term Neonates: Sonographic Study - Winchester, Patricia; Brill, Paula W.; Cooper, Rebecca; Krauss, Alfred N.; Peterson, Hart deC (American Journal of Neuroradiology, 1986)
The premature infant brain has been thoroughly studied by sonography, and normal standards for ventricular size have been established. Whether these apply to normal full-term infants is uncertain. Fifty-three healthy full-term infants were electively examined by real-time sonography through the anterior fontanelle on the first to sixth days of life. Nine had asymmetric lateral ventricles; two of these had unexpected evidence of intracranial hemorrhage, while a third had a ventricular cyst. Forty-four infants had symmetric ventricles, but in 36 the ventricles had little or no cerebrospinal fluid. Vaginal delivery had a statistically significant association with these ‘compressed’ lateral ventricles. This study indicates that seemingly healthy infants may have unsuspected intracranial hemorrhage, that asymmetric ventricular size may be normal, and that shortly after birth most healthy infants have “compressed” lateral ventricles that should not be interpreted as cerebral edema.